Thomas Schütte : united enemies - Schütte, Thomas, 1954-; Olof-Ors, Matilda, 1973-; Moderna museet (Stockholm, Sweden) (Stockholm : Moderna Museet ; London : Koenig Books, 2016)
Installations, architectural models, drawings, prints and gigantic sculptures are waiting for you at this autumn?s major exhibition. Thomas Schütte is one of the most seminal artists of his generation, and is known mainly for his sculptures. The exhibition 'Thomas Schütte. United enemies' takes the artist?s sculptural works from the past two decades as a starting point. Schütte explores shifts of scale ? juxtaposing the intimate and personal with the monumental. A colossal steel figure outside the museum entrance, Vater Staat (2010), observes visitors as they arrive. The key work in the exhibition ? the monumental bronze sculptures United Enemies (2011) ? originate in his small, sketchy figures with heads of modelling clay made nearly twenty years earlier. Thomas Schütte was born in 1954 in Oldenburg, north-west Germany. He was enrolled at the Kunstakademie Düsseldorf in 1973. Among his fellow students were many of today?s internationally acclaimed artists, including Thomas Ruff (b. 1958) and Katarina Fritsch (b. 1956). The works from his student years are distinctly influenced by 1970s minimalism and conceptualism. Exhibition: Moderna Museet, Stockholm, Sweden (08.10.2016-15.01.2017).
Catalog of an exhibition held at Moderna Museet, Oct. 8, 2016-Jan. 15, 2017.
boek
Keywords: Schütte, Thomas, -- 1954- -- Exhibitions; Schütte, Thomas, -- 1954-; Exhibition catalogs